Landscapes and Landforms of Hungary - Lóczy, Dénes (World Geomorphological Landscapes, 2015)
This volume is the first comprehensive description of the most spectacular landforms of Hungary. It is a richly illustrated book which presents a collection of significant sites, capturing the geodiversity of Hungarian landscapes. The Landscapes and Landforms of Hungary discusses the effects of geomorphological features to the landscape, such as volcanism, weathering, fluvial or aeolian erosion, karst formation, gravitational movements, and others. The importance of the conservation of geomorphological heritage is underlined, as well as the importance of geomorphological heritage and conservation. This book can be used for undergraduate and graduate courses in geomorphology, physical geography, hydrogeography, and nature conservation. It will be of benefit to environmental scientists, geomorphologists, conservationists, among others.